Corn planting - Cheney, James Hamilton (My University, 1906)
Introduction: In the raising of corn too much importance cannot be laid upon the selection of seed. The question often arises with farmers as to whether to select from their own fields or from those of a neighbor or whether to buy seed which has grown in some other section of the country. As a general proposition it may be said that unless the corn of a community is very poor it would be better to select home grown seed rather than to buy seed which was grown in a different climate or soil. In buying seed corn care should be taken to procure that which has come from a locality of similar climate, soil, and general conditions, such as length of season, rainfall, etc., to that in which it is to be grown. Importance of stalk, ear, and kernel in seed selection. The year book of the Department of Agriculture for 1902 contains an excellent discussion on this subject, from which I have made notes. In testing the advisability of considering the stalk, ear, and kernel in seed selection several experiments were performed. I. One stalk of 'Perfect Golden Beauty" variety was noticed to have very broad leaves. The ear of this stalk was hand-pollinated from the same stalk. The corn from this plant was planted and the resulting plants showed the same characteristics as did the parent plant. This was also the case with the second year's selection. A few short and very leafy plants were found in a field of tall growing white dent corn. These stalks were from 4-5 feet high, while the normal height of the variety was about 10 feet. A few of these short stalks were selected and cross-pollinated one with another. The resulting seed was planted in a row next to the normal stalks of the variety, The contrast between the normal and selected corn was very noticeable.
Citation: Cheney, James Hamilton. Corn planting. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Agriculture; Corn; Seed; Planting; Hybrids; Theses